Do Cellular Entry Mechanisms of SARS-Cov-2 Affect Myocardial Cells and Contribute to Cardiac Injury in COVID-19 Patients? - Balse, Elise; Hatem, Stéphane N. (Frontiers in Physiology, 2021)
Although the main vital organ affected by SARS CoV-2 is the lung, more than 20% of hospitalized patients show heart injury, however the underlying mechanisms are still actively investigated. Inflammation or myocardial ischemia are now well-established pathogenic factors. Direct cardiac damage by the virus is likely and might account for some aspects of cardiac diseases in COVID-19 patients. However, precise knowledge on mechanisms of virus entry and progression in host cells and notably in cardiac cells is necessary in order to define the broad spectrum of pathogenicity of SARS-Cov-2 on myocardium and to identify specific therapeutic targets. This review article will focus on the intracellular trafficking machinery, the “Trojan horse” of the virus.